(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Iron deficiency anemia is a common condition characterized by a lack of iron in the body, leading to a decrease in the production of red blood cells. One of the main symptoms of this condition is fatigue, but there are also complaints and associated conditions that can arise as a result of iron deficiency anemia.